P206 Cardiovascular risk knowledge in patients of South Asian origin living with rheumatoid arthritis: data from India and the UK. (20th April 2020) - Kumar, Kanta; Arya, Suvrat; Nightingale, Peter; Sheeran, Tom; Aggarwal, Amita
Abstract: Background: South Asians have a higher risk of cardiovascular disease (CVD). Rheumatoid arthritis (RA) increases the risk of premature atherosclerosis. Therefore, we compared the level of CVD risk knowledge among patients of South Asian origin with RA in India and in the UK. Methods: In this cross-sectional survey, patients of South Asian origin with RA from India and the UK were recruited from secondary care settings. Data were collected via Heart Disease Fact Questionnaire-Rheumatoid Arthritis (HDFQ-RA), a validated self-completion questionnaire. The HDFQ-RA was translated into Hindi and piloted among patients from South Asian background before use. Additionally, clinical and demographic data was collected. Results: Among 118 patients from each country, 84% were female and they had similar age, education level, employment status and co-morbidities. Patients from India had longer disease duration (5.5 years versus 4.1 years (p = 0.012) whereas those from the UK had higher disease activity score (4.0 + 0.8 versus 3.1 + 0.7, p < 0.01). Regarding modifiable risk factors for CVD only 44.6% from India and 45.4% in the UK were aware of them (p=ns). However, awareness of the link between RA and increased risk of CVD was even more limited (38.1% in India and 40.7% in UK (p=ns). Conclusion: Patients of South Asians origin with RA from both countries had limited knowledge about CVD risk. There is a need to educate them about CVD risk during consultation, as this will result in better outcomes. Disclosures: K. Kumar None. S. Arya None. P. Nightingale None. T. Sheeran None. A. Aggarwal None.